2021
DOI: 10.31557/apjcp.2021.22.11.3455
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cognitive Behavioral Therapy on Improving Anxiety, Depression, and Quality of Life in Pre-Diagnosed Lung Cancer Patients

Abstract: Some cancer patients develop mental health problems such as anxiety, depression, post-traumatic stress disorder, adjustment disorders, social phobia, and organic mental disorders (Yi and Syrjala, 2017).Lung cancer is the most common cause of cancer death worldwide. Every year, the number of deaths from lung cancer is higher than that from breast, colon, and prostate cancer. According to the World Health Organization's 2017 report, Lung cancer is a leading cause of 1.69 million cancer deaths. In the United Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
2
8
0
Order By: Relevance
“…Given the high FoP scores of newly diagnosed lung cancer patients, medical professionals should pay more attention and make a more significant effort to help the younger patients who are at risk for clinical FoP coping with the psychological problem. The interventions including cognitive behavior therapy [ 46 ], mindfulness-based cognitive therapy [ 47 ], acceptance and commitment therapy [ 48 ], and problem-solving therapy [ 49 ] are recommended. As general considerations, internet and professional guidance can be combined to give patients personalized support in the forms of short films, animations, pictures, face-to-face consultation, and telephone consultation.…”
Section: Discussionmentioning
confidence: 99%
“…Given the high FoP scores of newly diagnosed lung cancer patients, medical professionals should pay more attention and make a more significant effort to help the younger patients who are at risk for clinical FoP coping with the psychological problem. The interventions including cognitive behavior therapy [ 46 ], mindfulness-based cognitive therapy [ 47 ], acceptance and commitment therapy [ 48 ], and problem-solving therapy [ 49 ] are recommended. As general considerations, internet and professional guidance can be combined to give patients personalized support in the forms of short films, animations, pictures, face-to-face consultation, and telephone consultation.…”
Section: Discussionmentioning
confidence: 99%
“…These items are clinician-rated on a seven-point Likert scale and are summed to produce a total scale score ranging from 0 to 60, with higher scores reflecting greater depression severity. Depression severity can be categorized into normal (0-6), mild depression (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), moderate depression (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), and severe depression . This study used the highly reliable Korean version of MADRS [28].…”
Section: Measurementsmentioning
confidence: 99%
“…The total score is calculated by the sum of the scores obtained from each item. The severity of the anxiety can be categorized into normal (0-7), mild (8)(9)(10)(11)(12)(13)(14), moderate (15)(16)(17)(18)(19)(20)(21)(22)(23), and severe . This study used the highly reliable Korean version of HARS [30].…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Badr et al 8 found a significant alleviation of depression and anxiety in patients who received six sessions of telephone psychological counselling compared with the usual care group. In addition,cognitive–behavioural therapy9 and music therapy10 have been shown to improve negative emotions in patients with cancer.In routine practice, clinicians have a wide choice of psychological interventions. Although previous meta-analyses have provided an efficacy size among psychological interventions ranging from non-significance,11 12 small to medium,13 and medium to large significance,14 they used traditional meta-analysis methods which can only analyse the efficacy of one intervention.…”
Section: Introductionmentioning
confidence: 99%